Silent brain infarcts in chronic kidney disease patients with nonspecific neurological symptoms - P Sasanka; Dr. T. Jaya Chandra (International Journal of Medical Research and Review, 2021)
Introduction: Silent brain infarcts (SBI) are parenchymal lesions of previous infarcts, classified as type III cerebrovascular disorder. A study was undertaken to find the relation between SBIs and nonspecific neurological complaints, an association of high sensitivity C-reactive protein (hsCRP) with silent brain infarcts. Methodology: It was a cross-sectional study conducted in the department of Nephrology, GSL Medical College, from January to December 2020. Individuals aged > 18 years with nonspecific neurological complaints were included. MRI brain, hsCRP and electrocardiogram were also carried as per the standard protocol. Fischer exact test was used to find the statistical significance; P < 0.05 was considered statistically significant. Results: A total of 51 members have included the male-female ratio was 1.04. SBI was presented in 27.4% (14). Age-wise, among the cortical SBI patients, maximum (75%) were in the> 61 years group. High density lipoprotein levels were > 40 mg/dL in 39.2%, normal triglycerides (TGL) were observed in 71% and raised hsCRP in 62.7% (32). Statistically, there was no significant difference in TGL levels. hsCRP levels were raised in 3 (75%) members with cortical SBI; statistically, there was no significant difference. Conclusion: The traditional risk factors associated with stroke were present in the patients with SBI. hsCRP was raised in chronic kidney disease patients having NSCL and having SBI.